A Novel Optimal Online Scheduling Scheme for Flexible Manufacturing Systems ⁎The authors wish to acknowledge the funding provided by the Federal Ministry of Education and Research Germany – Research Campus ARENA2036. Issue 10 (2019) - Wenzelburger, Philipp; Allgöwer, Frank
Abstract: With increasing demand of flexible production facilities, the scheduling of flexible manufacturing system has become a key challenge of modern manufacturing We present an approach to solve this problem for a class of flexible manufacturing systems by means of Model Predictive Control (MPC). In Wenzelburger and Allgöwer (2019), a modeling framework was proposed that automatically generates a model of the manufacturing system, which we use as basis for our approach. We introduce an MPC scheme that computes the optimal schedule for the manufacturing problem with respect to a given cost function. The presented scheme is guaranteed to find a solution in which all orders present in the manufacturing system will be fulfilled and therefore the overall production problem is solved. The MPC scheme is shown to be flexible enough to cope with orders of unknown type arriving during runtime, which is a drastic change of the production problem that cannot be handled seamlessly with classical approaches. The guarantees, which are given by the Model Predictive Controller for the original production problem, are preserved despite those changes and the completion of all orders is still guaranteed.